Isaac Bashevis Singer. - Siegel, Ben, 1925-2010 (University of Minnesota pamphlets on American writers, 1969)
Isaac Bashevis Singer - American Writers 86 was first published in 1969. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions.